ANALYSIS OF MANAGEMENT KNOWLEDGE IN HANDLING 2019 CORONA DISEASE PANDEMIC AT SUKARAME HEALTH CENTER, DISTRICT OF NORTH LABUHAN BATU IN 2022 - Tengku Mestika Mayang; Marice Simarmata (JURNAL KESMAS DAN GIZI (JKG), 2023)
Background: WHO stated that Europe has become the center of the Coronavirus pandemic. Because more cases and deaths from Covid-19 have occurred in Europe. The number of patients infected with Coronavirus disease has reached 2.24 million people in the world. The United States is the country with the largest number of Covid-19 contributors in the world, with around 700 thousand people. The Coronavirus disease 2019 pandemic has existed in 185 countries and killed 153,822 people. At present, the total number of sufferers of Coronavirus disease in the world is 382 million people, of which the United States 75.4 million, India 41.6 million, Brazil 25.6 million, France 19.1 million, the United Kingdom 17.4 million (WHO, 2022 ). Objective: To analyze management knowledge in handling the 2019 coronavirus pandemic at the Sukarame Public Health Center in Labuhan Batu Utara Regency in 2022. Methods: This study used a qualitative approach. This research is comprehensive, dynamic, and does not generalize. Results: This research was directed at how the Sukarame Health Center in Labuhan Batu Utara handled the spread of Covid 19. The impact of Covid 19 greatly disrupted the health, economic, social, and cultural sectors. Therefore, the role of the Puskesmas must have a good strategy for suppressing the spread of Covid-19 which is very important.